Pattern of bacterial and viral nasal colonies in preterm infants on nasal continuous positive airway pressure in neonatal intensive care units - Ramy Saleh Morsy; Amany Elkholy; Magda Badawy; Reem Nabil Said (Cairo : Ramy Saleh Morsy, 2013)
To support breathing of premature infants , there has been a trend toward less tracheal intubation , less mechanical ventilation and more nasal continuous positive airway pressure (CPAP) . Although the use of mechanical ventilation is a known risk for ventilator associated pneumonia , the relationship between CPAP and infections has not been adequately examined
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: CPAP; Preterm infants; Sepsis